Inhibitory effect of Weissella cibariaisolates on the production of volatile sulphur compounds - Mi-Sun Kang (journal of clinical periodontology, 2006)
Aims: The objective of this study was to characterize the inhibitory effects of Weissella cibaria isolates on volatile sulphur compounds (VSC) production both in vitro and in vivo. Material and Methods: We isolated and identified three hydrogen peroxidegenerating lactobacilli from children’s saliva, and assessed their inhibitory effects on VSC production and Fusobacterium nucleatum proliferation. Clinical studies were conducted with 46 subjects in order to measure the VSC of their mouth air. Results: These lactobacilli were identified as W. cibaria. These isolates inhibited the production of VSC by F. nucleatum (po0.05). The concentration of F. nucleatum was decreased by 5-log cycles as a result of exposure to the W. cibaria strains (po0.05), whereas the catalase-treated W. cibaria cultures exerted no evident inhibitory effects on F. nucleatum replication. In the clinical studies, gargling with one isolate resulted in a significant reduction in the levels of H2S and CH3SH by approximately 48.2% (po0.01) and 59.4% (po0.05), respectively. Conclusions: These results indicate that W. cibaria isolates possess the ability to inhibit VSC production under both in vitro and in vivo conditions, demonstrating that they bear the potential for development into novel probiotics for use in the oral cavity.